# INTEGRATION [Solved!]

**phinah** 21 Dec 2017, 14:11

### My question

Section 8, Integration by Trig Sub, Exercise 3:

We are not clear as to why you have + 1 in the solution.

### Relevant page

8. Integration by Trigonometric Substitution

### What I've done so far

Because the integral is of the form `x^2 - a^2` after completing the square, we used x = a `sec theta` with a = 1. Setting up the triangle, x is the hypotenuse, 1 is the adjacent side, and `sqrt (x^2+2x)` is the opposite side.

Therefore secant = x and tan = `sqrt (x^2+2x)` should be substituted into the integral of sec x to obtain the final answer.

X

Section 8, Integration by Trig Sub, Exercise 3:
We are not clear as to why you have + 1 in the solution.

Relevant page
<a href="https://www.intmath.com/methods-integration/8-integration-trigonometric-substitution.php">8. Integration by Trigonometric Substitution</a>
What I've done so far
Because the integral is of the form `x^2 - a^2` after completing the square, we used x = a `sec theta` with a = 1. Setting up the triangle, x is the hypotenuse, 1 is the adjacent side, and `sqrt (x^2+2x)` is the opposite side.
Therefore secant = x and tan = `sqrt (x^2+2x)` should be substituted into the integral of sec x to obtain the final answer.

## Re: INTEGRATION

**Murray** 03 Nov 2019, 03:02

I don't know why this question was missed. So sorry!

I gather you mean the "+1" in the line

"The triangle in this case starts with `x+1= sec theta + 1`"

Right?

Because I substituted `u=x+1` and we chose `u = sec theta` earlier in the problem, then we'll have:

`u = x+1 = sec theta + 1"

Looking at your solution, I agree with using `a sec theta`, but it should be like this:

Because the integral is of the form `X^2 - a^2` after completing the square (with `X = x+1`), we use

`X = a sec theta` with `a = 1.` That is, `x+1 = sec theta.`

The triangle will now be as I have in the solution.

Hope it helps.

X

I don't know why this question was missed. So sorry!
I gather you mean the "+1" in the line
"The triangle in this case starts with `x+1= sec theta + 1`"
Right?
Because I substituted `u=x+1` and we chose `u = sec theta` earlier in the problem, then we'll have:
`u = x+1 = sec theta + 1"
Looking at your solution, I agree with using `a sec theta`, but it should be like this:
Because the integral is of the form `X^2 - a^2` after completing the square (with `X = x+1`), we use
`X = a sec theta` with `a = 1.` That is, `x+1 = sec theta.`
The triangle will now be as I have in the solution.
Hope it helps.

You need to be logged in to reply.